Perceived Quality of Life among Elders; a role of Family Support - Azniah Syam; Andi Asmaul Husna; Indra Dewi (Lembaga Penelitian dan Pengabdian Masyarakat Stikes Panrita Husada Bulukumba, 2023)
The aging population and the prevalence of chronic disorders among the elderly have led to an increased demand for in-home care services. Maintaining quality of life (QoL) for the elderly is a primary goal of aged care services. This study aims to understand the perceptions of elderly individuals regarding their QoL and the optimal support provided by their families. Methods: A cross-sectional research design was used, and data were collected from 93 elderly individuals in the Patallassang District of Gowa Regency, Indonesia. The World Health Organization Quality of Life (WHO-QoL) instrument and the Family Support Scale (FSS) questionnaire were employed to assess QoL and family support, respectively. The results showed a positive correlation between family support and QoL, indicating that greater support from families leads to a higher QoL for the elderly. Furthermore, educational background and family composition were identified as factors influencing the impact of family support on QoL. Conclusion, The findings highlight the importance of tailored care models and support services to meet the specific needs of elderly individuals, particularly those with chronic ailments. Understanding the perspectives of the elderly and their support requirements is crucial for developing effective strategies to enhance their independence and well-being.